Analysis of Implementation of the Chronic Disease Management Program (PROLANIS) Diabetes Mellitus Type 2 (DMT2) during the Covid-19 Pandemic at the West Lombok District Health Center - Atmaja, I Nengah Dwi Jendra (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The Chronic Disease Management Program (PROLANIS) is implemented by Health Social Security Administering Agency (BPJS Kesehatan) in an integrated manner involving participants, health facilities, and BPJS Kesehatan in order to maintain the health of participants with chronic diseases, especially Diabetes Militus Type 2 (DMT2). It is aimed at sufferers to achieve a better quality of life. The cost of effective and efficient health services is an important factor, because it is one of the performance-based capitation indicators in Community Health Centers (Puskesmas). Based on data from the West Lombok Health Office, West Nusa Tenggara province - Indonesia, from the top 10 most diseases, diabetes mellitus ranks 8 (eight), where in 2019 there were 8.882 cases, while in 2020 there were 9.683. The purpose of this study is to analyze the input, process and output factors of the PROLANIS program at the Puskesmas. This study is a descriptive study with qualitative and quantitative approaches, where primary data was obtained from in-depth interviews and secondary data from the Pcare Puskesmas application. The results showed that the input of PROLANIS registered participants was still very low (about 14% of the total number of participants diagnosed with DM), the process indicator of the number of PROLANIS participants who visited the puskesmas was quite high (82%), and the output indicator showed the number or ratio of participants whose blood sugar was controlled, is still very low (26%). Finally, in general, our findings are that the implementation of PROLANIS at the West Lombok District Health Center during the Covid-19 Pandemic is still not optimal in terms of input, process, and output.